Peri-saccadic compression to two locations in a two-target choice saccade task - Lappe, Markus; Hamker, Fred H. (Frontiers in Systems Neuroscience, 2015)
When visual stimuli are presented at the onset of a saccadic eye movement they are seen compressed onto the target location of the saccade. This peri-saccadic compression is believed to result from internal feedback pathways between oculomotor and visual areas of the brain that enhance vision around the saccade target at the expense of localization ability in other regions of the visual field. Although saccades can be targeted at only one object at a time, often multiple potential targets are available in a visual scene, and the oculomotor system has to choose which target to look at. If two targets are available, preparatory activity builds-up at both target locations in oculomotor maps. Here we show that in this situation two foci of compression develop, independent of which of the two targets is eventually chosen for the saccade. Our results suggest that theories that use oculomotor feedback as efference copy signals for upcoming eye movements should take the possibility into account that multiple feedback signals from potential targets may occur in parallel before the execution of a saccade.